Testing alien plant distribution and habitat invasibility in mountain ecosystems: growth form matters - Giorgis, Melisa Adriana (2016)
Most studies focused on understanding habitat invasibility use the current levels of invasion as a direct proxy of habitat invasibility. This has shown to be biased by the influence of propagule pressure and climate. We suggest that plant growth forms need to be considered as an extra factor, as habitat preferences might not be equal for all potential invaders. We test the influence of propagule pressure, climate and habitat characteristics on the current level of invasion and habitat invasibility, specifically addressing whether an analysis focused on growth forms evidence different patterns than the total pool of alien species. We used 499 floristic vegetation plots located in Córdoba Mountains. We used proportional alien richness of the total pool and for each growth form as response variables. We identified models that best explained current levels of invasion. We used the residuals of the models with propagule pressure and climate as the response variable. Then, we performed linear models to test the relationship between habitat characteristics and the residuals of the models. We found different drivers of current alien distribution patterns for the total pool and each growth form. Habitat invasibility was not equal when quantified for the total pool or growth forms. Shrublands and outcrops were recorded as less susceptible to woody invasion, while grasslands and native woodlands were resistant to the invasion of grasses and none habitat type was resistant to the invasion of forbs. We highlight that the current level of invasion and habitat invasibility are highly growth form dependent.